Response times for reflexive saccades correlate with cognition in parkinson's disease, not disease severity or duration - Yu, Yaqin; Yan, Weihong; Xu, Xin; Zhang, Kaili; Si, Lihong; Liu, Xiaolei; Wang, Jinyu; Song, Junling; Sun, Huanxin; Li, Xinyi (Frontiers in Neurology, 2022)
Objective Dementia is a common and serious non-motor symptom in Parkinson's disease (PD). We aimed to investigate the reflexive saccade in PD patients and explore its potential role as a biomarker for cognitive decline. Methods Using an infrared video-based eye tracker, we investigated reflexive saccades in 94 PD patients and 115 healthy controls (HCs). Saccadic parameters were compared between PD patients and HCs, and also among PD subgroups. The correlation of saccadic performance with disease duration, severity and cognition were further investigated. Results Compared with healthy controls, PD patients had prolonged and hypometric reflexive saccades even in early disease stage. Univariate and multivariate analysis showed that there was significant inverse relation between prolonged latency and MMSE in PD patients (P < 0.05); tremor dominant PD patients were more likely to have decreased velocity than non-tremor-dominant PD patients (P < 0.05); saccadic accuracy was found to have no significant relation with disease duration, H&Y staging or MMSE. Conclusion Reflexive saccadic performance was abnormal in PD and worsened with cognitive decline. The negative correlation between prolonged latency and MMSE scores may make the reflexive saccade a potential predictor for cognitive decline in Parkinson's disease.